Effects of coated and incorporated N-(n-butyl) thiophosphoric triamide urea-nitrogen dynamics in soils on growth and yield of maize (Zea mays L. var. thai super sweet) - Mohd Zuki, Muhammad Muhaymin (2020)
Urea fertilizer is the most convenient nitrogen (N) fertilizer commonly being applied to soils for crop production due to its high N percentage (46%). Nonetheless, N in urea could be lost due to rapid hydrolysis which resulted in increased N loss through ammonia volatilization, leaching and denitrification. Currently, urea fertilizer treated with N-(n-butyl) thiophosphoric triamide (NBPT) has been developed to overcome loss of nitrogen from urea by inhibiting the urease activity which slow down urea hydrolysis. However, the effectiveness of urea treated with NBPT on crops in Malaysian highly weathered soils are not known. Thus, this research was undertaken to study N transformation and volatilization from NBPT treated urea fertilizer comprising of NBPT coated urea (NCU) and NBPT incorporated urea (NIU) in selected Malaysian soils, as well as to determine their effects on nitrogen use efficiency (NUE), N uptake and growth of maize under field conditions. Laboratory trials were conducted to study N mineralization, volatilization and soil leaching from three types of fertilizers (NCU, NIU and urea) in three different soil series (Morib, Bungor and Serdang). Results indicated after 7 days of incubation, all NCU and NIU treated soils showed significantly (P≤0.05) higher total inorganic N and reduced NH3 volatilization by 45.13% - 53.27% compared to untreated urea. The resulted on soil leaching showed that NBPT treated urea had higher ammonium content compared to urea during 3rd – 4 th pore volume. With regards to soil series, Bungor was found to have more inorganic N and reduced NH3 losses than Serdang and Morib. It showed that NCU and NIU had capability to reduce ammonia volatilization losses in all three different soil series. For the first field study, maize plant were subjected to six treatments: two of which were controls, T0 = unfertilized and T1 = 120 kg N ha-1 of urea, and four NCU treatments at 144 kg N ha-1 (T2), 120 kg N ha-1 (T3), 96 kg N ha-1 (T4) and 72 kg N ha-1 (T5). Plant growth, yield, N uptake, NUE and soil inorganic N were measured at v6 (32 DAP), v10 (53 DAP), VT (60 DAP) and harvesting time (79 DAP). Relatively, NCU at 120 kg N ha-1 and 96 kg N ha-1 were effective in increasing growth, yield, N uptake and NUE. Improvement of NUE by 45% over urea was recorded in the treatment of NCU at 96 kg N ha-1 . This showed that almost 20% of fertilizer usage could be saved rather than the usual 120 kg N ha-1 . While in second field study, T1 (control) and best 3 NCU treatments (T3, T4 and T5) from first field study were selected and further tested and compared to NIU at similar rate as T3, T4 and T5. Growth data were measured 1 week after basal fertilization (21 DAP), 1 week after side dressing (49 DAP) and harvesting time (75 DAP) which included plant growth, yield and N uptake. Results demonstrated that NCU and NIU treatments at 120 kg N ha-1 and 96 kg N ha-1 significantly (P≤0.05) increased maize growth and yield compared to untreated urea. Also, our findings exhibited no significant difference (P>0.05) between NCU and NIU at 120 kg N ha-1 and 96 kg N ha-1 . Thus, NIU at 96 kg N ha-1 was recommended as it could prolonged more storage time compared to NCU. This study provided evidences that NBPT can reduce N loss, thus ensuring more N for longer period in soils, enabling more N available for plant N uptake, hence promote growth and yield for grain crop in highly weathered soils.